Revalidation of an endemic Cuban Skipper, Chiomara gundlachi (Lepidoptera: Hesperiidae) - Núñez, Rayner; Norriss, Tim; Fernández, Douglas M.; Hausmann, Axel (Zootaxa, 2018)
In the present work we reassess the taxonomic status of one species of Hesperiidae, subfamily Pyrginae, originally described from Cuba. As part of a larger project on the Greater Antillean butterflies, we obtained COI barcode sequences for Cuban specimens of Chiomara mithrax (Möschler, 1879). The comparison of these sequences revealed deep divergences from others belonging to continental specimens. Inspired by these results we performed morphological comparisons including genitalia structures, which revealed correlating differences between specimens from Cuba and the continent. Therefore, we propose the necessary changes in its taxonomy.